On the variation of the belt and chiral screw and spring conformations of substituted regioregular HT undecathiophenes. Issue 4 (9th January 2018) - Dobrowolski, Jan Cz.; Jamróz, Małgorzata E.
Abstract : The stability and characteristics of shape and π-electron delocalization of a belt- and two chiral screw- and spring-conformers of HT regioregular substituted undecathiophenes was calculated. Abstract : The stability of a belt- and two chiral screw- and spring-conformers of HT regioregular substituted undecathiophenes was calculated. For many substituents these conformers can possibly coexist. The averaged SCCS torsion angle and HOMA index characterized well the geometry and π-electron delocalization. The substituent volume appeared to shape the conformer form and stability.